Rapid lateral flow immunoassay for fluorescence detection of canine distemper virus (CDV) - Cao, Zhigang; Yi, Li; Liu, Xiangnan; Shang, Jinyuan; Cheng, Yuening; Feng, Erkai; Liu, Xingyu; Fan, Yuping; Hu, Xiaoliang; Cai, Wenlong; Cong, Feng; Cheng, Shipeng (Frontiers in Veterinary Science, 2024)
Canine distemper virus (CDV) is a highly contagious and potentially lethal virus that affects dogs and other members of the Canidae family, including wolves, foxes, and coyotes. Here, we present a fluorescent lateral flow immunoassay (FLFA) platform for the detection of CDV, which utilizes fluorescent microspheres -fusion protein monoclonal antibody (mAb)-labeled monoclonal antibody. The assay detected CDV within 5 min, with a detection limit threshold of 3×10 2 TCID50/mL. Notably, the assay demonstrated no cross-reactivity with canine parvovirus, canine coronavirus, canine adenovirus, feline calicivirus, feline herpesvirus, or feline parvovirus. Field and clinical applicability of the assay was evaluated using 63 field samples, including 30 canine fecal samples, 18 swab samples, and 15 blood samples. The coincidence rate between the detection results of clinical samples obtained through FLFA and reverse transcription polymerase chain reaction (RT-PCR) was 96.83%. Thus, this assay offers a significant advancement for the rapid diagnosis of CDV at the point of care.